Manejo del psílido de la papa - Pérez, W.; Gamarra, H.; Andrade-Piedra, J.L. (International Potato Center, 2022)
A Potato Psyllid Manual was developed (in spanish) with the aim of providing updated information on the Bactericera cockerelli pest to agricultural professionals and technicians from countries or regions where this quarantine insect is not present or there is an imminent risk of its entry. In this manual we describe the different components of integrated insect/pathogen management, such as insecticide applications specific to the phenological state of the insect present in the crop field, applications of biorational products, insect monitoring, use of tolerant varieties, use of seed certified, legal aspects, among other details. It is expected that this manual will be adapted to other contexts and the recommendations, especially on chemical and legal products, will be made in accordance with the national regulations in force in each country.